Seasonal Pattern Analysis In Bolu House Sales Using Seasonal Adjustment Method - Andrean, Stefhany; Sembiring, Muhammad Ardiansyah; Sena, Maulana Dwi (JURNAL RISET KOMPUTER (JURIKOM), 2025)
Rumah Bolu is a business engaged in the sale of sponge cakes located on Jalan Perumahan Duta Mas 9, Sei Kamah II, Kec. Sei Dadap, Asahan Regency, North Sumatra 21263. The problems faced by Rumah Bolu include if the stock decreases, Rumah Bolu risks losing sales and customer trust, while if the stock is excessive but sales are low it can cause wasteful costs, decreased product quality and financial losses that hinder maximum profits. During certain seasons such as weekends or big celebrations, the demand for sponge cakes can increase drastically which risks causing shortages of raw material stock and delays in marketing. Conversely, on Monday to Friday, sales tend to decrease which can result in stock piling up and increase the risk of loss. With the need for a forecasting system, Rumah Bolu can adjust sales based on seasonal demand patterns so as to avoid the risk of shortages or excess stock, optimize operational costs and increase profits to the maximum. To predict the sale of sponge cake, a forecasting method is applied, namely the Seasonal Adjustment method, which is used when the time series data pattern obtained has a seasonal pattern. The seasonal pattern is a fairly unique sales pattern because it can be seen when there is a certain increase in a certain season. The purpose of this study is to design a sponge cake stock forecasting application with the Seasonal Adjustment method and to apply a forecasting method to predict the stock of sponge cakes at Rumah Bolu using PHP and its MySQL database. The research method used in this study is a quantitative research method. The results of the Seasonal Adjustment calculation prediction on banana sponge cakes for the January 2025 period were 424 with a MAPE of 5.53%. Then the results of the Seasonal Adjustment calculation prediction on pandan sponge cakes for the January 2025 period were 73.67 with a MAPE of 3.84% and the results of the Seasonal Adjustment calculation prediction on birthday sponge cakes for the January 2025 period were 142.67 with a MAPE of 3.03%.